Neurodiversity in the Workplace Interests, Issues, and Opportunities - Bruyère, Susanne M.; Colella, Adrienne (SIOP Organizational Frontiers Series, 2023)
Neurodiversity in the Workplace presents a timely and needed perspective on the role and responsibility of employers and those working to increase the effectiveness of workplace practices to examine the many ways we preclude large segments of the population from employment; minimizing opportunities for building a truly inclusive work environment. This collection provides an opportunity to look at how discrimination can occur across the employment process and what can be done to minimize the exclusionary practices that prevent neurodiverse individuals from getting into the workplace, advancing, thriving, and contributing as each of us desires to do. With expertise from leading professionals, this book provides a holistic look at the application of leadership theories in a neurodiverse context and how the workplace can be adapted to accommodate for neurodiverse employees. This book also explores effective recruitment strategies by looking into applicant screening as well as interviewing and selection, adapting internal organizational resources to a neurodiverse workforce, and legal and regulatory environment considerations for autism hiring programs. Each chapter provides an overview of existing knowledge on effective workplace inclusion practices across the employment process, specific implications of research to date for a more neurodiversity-inclusive workplace, and what future research is needed to further inform these practices. This volume is intended to increase awareness about the challenges and opportunities in making the workplace more neurodiversity-inclusive, making it instrumental for I/O and other psychologists. This book is also crucial for management and business consultants; employers; diversity, equity, and inclusion specialists; human resource professionals; and others interested in neurodiversity inclusion more broadly.